STRATEGI GURU DALAM MENANAMKAN KARAKTER CINTA TANAH AIR DAN SEMANGAT KEBANGSAAN PESERTA DIDIK DI SEKOLAH DASAR NEGERI 104230 TANJUNG SARI KECAMATAN BATANG KUIS - Lubis, Sartika Eka Fitri (At-Tazakki: Jurnal Kajian Ilmu Pendidikan Islam dan Humaniora, 2023)
Abstract: Schools as institutions in education have a very important role in realizing quality human resources. Education is an effort to shape behavior and character in a continuous, directed and systematic manner. This research used a qualitative approach. The research method used in this research is field research. Data collection techniques through observation, interviews and documentation. To determine the validity of the data required inspection techniques, implementation. The implementation of inspection techniques is based on a number of certain criteria. There are four criteria used, namely the degree of trust (credibility), transferability (transferability), dependability (dependability), and certainty). The results in this study show that: 1) The teacher's strategy in the character of love for the motherland and national spirit is in the form of: a) exemplary, b) stories, c) discussion, d) reward and punishment, and e) collaboration between teachers with parents. 2) In applying the character of love for the motherland and national spirit to students, the teacher has supporting factors. Supporting factors are the learning styles of students in good learning, the existence of learning media, the existence of good cooperation between teachers and parents or guardians of students which leads to the formation of the character of the national spirit and love of the students' homeland.